Uniportal video assisted thoracic surgery with 2 cm skin incision for right middle lobectomy with systematic lymphadenectomy - Liu, Ruijun; Tan, Qiang; Huang, Jia; Li, Jiantao; Luo, Qingquan (Journal of Thoracic Disease, 2017)
Today, video-assisted thoracic surgery (VATS) was very popular and more and more common, which could be carried out at all levels of medical centers, most of which used multiple-ports VATS techniques. However, uniportal VATS was more difficult technique compared with multiple-ports VATS, and was not yet completely universal. Uniportal port VATS with 2 cm incision was more difficult surgery, and asked the surgeon to master more surgical techniques and good collaborations with each other, however, which not only could reduce the postoperative pain and skin numbness but supply cosmetology and psychological comfort for patients. To reduce unnecessary damage to patients, we minimized the incision to 2 cm. Therefore, we called it precise uniportal port VATS technique in our surgical center and introduced it here.